Gerakan Masyarakat Sadar Sampah: Edukasi Pengelolaan Sampah Rumah Tangga Ramah Lingkungan - Farha Assagaff; Kasman Lestaluhu; Irdan Irdan; Fitriah Suryani Jamin; Lely Meriaya Sari (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Household waste is a growing environmental issue in line with population growth and changes in consumption patterns. Improper waste management can have negative impacts on health and the environment. This Community Service activity aims to increase public knowledge and awareness regarding environmentally friendly household waste management through a waste-aware community movement. Implementation methods include outreach, education, waste sorting demonstrations, and community mentoring. The results of the activity indicate an increase in community knowledge and skills in sorting and managing household waste, as well as the formation of positive attitudes toward clean living and environmental awareness. This program is expected to be the first step in creating a clean, healthy, and sustainable environment.